Impact of wealth inequality on child nutrition in Bangladesh - Mortuza Ahmmed (Paediatrica Indonesiana, 2013)
Background The prevalence of malnutrition in Bangladesh isamong the highest in the world. Millions of women and childrensuffer from one or more forms of main utrition, including low birthweight, wasting, stunting, underweight, vitamin A deficiency,iodine deficiency disorders, and anemia. Today malnutritionnot only affects individuals, but its effects are passed from onegeneration to the next as malnourished mothers give birth toinfants wh o struggle to develop and thrive.Objective To assess the economic impact on child nutrition inBangladesh.Methods The 2011 Bangladesh Demographic Health Survey datawas used for this study. In this study, quintiles were calculatedbased on asset and wealth scores by use of principal componentanalysis. To understand the nutritional status and healthinequality, concentration index was also calculated.Results The negative concentration index showed a higher rateof malnutrition in the children less than five years of age from thepoorest class. Furthermore, the ratio of poorest to richest indicatedthat stunting and underweight conditions in rural children underfive years of age were almost two times higher than that of therichest children. This inequality in the health situation of childrenmay be explained in terms of income inequality. In Bangladesh,about 40% of the wealth is concentrated in 10% of the families.The results are discussed as possible input for public policy.Conclusion Bangladeshi children under the age of five yearsand in the poorest economic class are nearly twice as likely to beunderweight or stunted compared to children of similar age in therichest economic class